A Type of Fuzzy T-S Controller for a Nonlinear MIMO Dynamic Plant - Dworak, P. (Elektronika ir Elektrotechnika, 2014)
In the paper a control system utilizing Takagi-Sugeno (T-S) fuzzy rules for a MIMO nonlinear dynamic plant is presented. In the proposed control system use is made of a set of linear modal controllers that create a multi-controller structure from which a group of controllers appropriate to given operation conditions is chosen and used to calculate, by employing T-S fuzzy rules, control signals. Stability conditions of the closed-loop system may be checked by the use of the simple, well-known techniques thus the proposed method allows one to simplify the synthesis of the controller. Problems of the controller practical realization and its implementation in, for example, constrained memory of programmable automation devices are discussed. The final part of the paper includes simulation results of system operation with an adaptive controller of (stepwise) varying parameters along with conclusions and final remarks. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7091